2021
DOI: 10.1681/asn.2020071074
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of Renal Arteritis in ANCA-associated Vasculitis: Clinical Characteristics, Pathology, and Outcome

Abstract: Background Renal involvement in antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is associated with poor outcomes. The clinical significance of arteritis of the small kidney arteries has not been evaluated in detail. Methods In a multicenter cohort of AAV patients with renal involvement, we sought to describe the clinicopathologic characteristics of patients with AAV who had renal arteritis at diagnosis and to retrospectively analyze their prognostic value. Results We included 251 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 34 publications
4
30
0
1
Order By: Relevance
“…Few studies have compared the prognostic value of the histopathological classification and RRS ( 22 , 23 ). Using the histopathological classification or RRS, we observed in our cohort survivals similar to those reported in the original studies and subsequent confirmation cohorts ( 12 , 13 , 22 – 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have compared the prognostic value of the histopathological classification and RRS ( 22 , 23 ). Using the histopathological classification or RRS, we observed in our cohort survivals similar to those reported in the original studies and subsequent confirmation cohorts ( 12 , 13 , 22 – 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike Berden's classification, Brix et al in 2018 suggested the ANCA renal risk score (ARRS) by incorporation of baseline glomerular filtration rate (GFR) to the histopathological findings (percentage of normal glomeruli, tubular atrophy/interstitial fibrosis) to predict ESKD in patients with AAV (6). Recently, interstitial vasculitis has been shown to improve long-term outcome prediction in ANCA GN in both scoring systems (42). These observations underscore the pathogenic role of interstitial vasculitis in ANCA GN, and our findings of more minor vasculitis manifestations in peritubular capillaries in females further improve our understanding of sex differences in AAV.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 30 potentially eligible reports were further evaluated. After excluding the articles with irrelevant contents and articles with no full-text and insufficient data, we included 12 distinct cohorts from 11 articles ( 11 , 19 28 ) in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%